An annotated checklist of the Collembolan fauna of Thailand - Jantarit, Sopark; Bedos, Anne; Deharveng, Louis (Zootaxa, 2016)
The current knowledge of the Collembolan fauna of Thailand is reported here, based on the checklist of Bedos (1994) completed by data on several taxa described since this date, with an update of the taxonomic status of the species. A total of 194 species from 53 genera and 14 families are listed, that were mostly discovered and described during the last three decades. The updated checklist illustrates a strong unevenness in sampling efforts across space and habitats, and in the degree of taxonomic coverage of the different families of the group. Geographically, only the Doi Inthanon massif can be considered as relatively well known, but even there the species in several major habitats and microhabitats have not been sampled. Data are lacking or much more limited for all other regions of the country. The species richness of Thailand is undoubtedly much more than observed number.